Studi Pembuatan Kelas Bonita pada Tegakan Acacia mangium Willd. di PT. Musi Hutan Persada, Sumatera Selatan - Heru Budi Santoso; Ronggo Sadono; Ari Susanti (Fakultas Kehutanan Universitas Gadjah Mada, 2008)
Study on the Determination of Site Quality Index for Acacia mangium Willd. in PT Musi Hutan Persada, South SumatraSite index is required to estimate forest productivity. This study was conducted to generate a diameter-height model and use it to construct a direct site quality index for Acacia mangium Willd. stands without thinning by dominant height approach in PT. Musi Hutan Persada,South Sumatra. It comprises two phases, namely dominant height curve development and site index construction based on semi-permanent and permanent plots data. The regression analysis of maximum diameter was employed to estimate the dominant height. The accepted diameter-height model was used for modeling an anomorphic site index using Schumacher’s formula. Dominant height could be estimated using the equation:Ln h = 3.588 - (6.955/d) , (R2 = 0.91, sum of square error = 0.24), where h : dominant tree height and d: stem diameter.The equation was then used to modeling site index of A. mangium stands with age index of 6-years. The proposed model was :